The Emerging Role of Obesity, Diet and Lipid Metabolism in Prostate Cancer - Matteo Ferro; Daniela Terracciano; Carlo Buonerba; Giuseppe Lucarelli; Danilo Bottero; Sisto Perdonà; Riccardo Autorino; Alessandro Serino; Francesco Cantiello; Rocco Damiano; Iulia Andraş; Sabino De Placido; et al. (2016)
Obesity is associated with an increased risk of a number of serious medical conditions, including cancer. As far as prostate cancer is concerned, obesity is associated with an increased risk of high-grade tumors, which is possibly related to lower androgen levels. Diet may also affect prostate cancer risk since countries with a higher dietary fat intake also present higher prostate cancer mortality rates. Interestingly, prostate cancer is associated with a number of metabolic alterations that may provide valuable diagnostic and therapeutic targets. This review explores the available clinical as well as biological evidence supporting the relationship between obesity, diet, alteration in metabolic pathways and prostate cancer.